A case study using the New Ecological Paradigm scale to evaluate coastal and marine environmental perception in the Greater São Paulo (Brazil). (15th June 2020) - Barradas, Juliana Imenis; Ghilardi-Lopes, Natalia Pirani
Abstract: The individuals' perception may vary according to their values and life experiences, thus, the goal of the present study was to evaluate if the relationship to coastal areas (work, research and leisure) and frequency of beach attendance would influence the environmental perception of people living in greater São Paulo (Brazil). The environmental values were measured using online questionnaires based on the New Ecological Paradigm (NEP) scale (adapted to coastal and marine environments) and considering that the type of relation with the coastal environment could alter their level of perception. A total of 386 participants answered the questionnaires and the results showed mainly a pro-NEP attitude of all respondents, However, people that establish some kind of relationship to marine environment presented significantly higher scores. In general, although they were conscious that we are reaching the Earth's limit and that the human interference on the environment is mainly negative, there was still a belief that human beings are able to dominate nature and in the inexhaustibility of marine resources, once we know how to handle it. Besides that, most respondents think that climate change; sea level rise and ocean acidification has been treated with exaggerated concern. The results also showed that age and educational level significantly influenced the participants' performance in the test. Therefore, we conclude that there is a necessity of educational investment from the beginning of the school age on and the importance of good quality in scientific dissemination. Graphical abstract: Image 1 Highlights: For most respondents, current environmental changes have been treated with exaggerated concern. People's environmental are related to the relationship to coastal areas. The grouping variable reflected different marine environmental perception. There's still a belief that man can rule the nature. Educational background and scientific dissemination in Brazil are still unsatisfying.